OPTIMALISASI PENGELOLAAN PAJAK BUMI DAN BANGUNAN SEBAGAI PENDAPATAN ASLI DAERAH KOTA PEKANBARU BERDASARKAN PERATURAN DAERAH NOMOR 8 TAHUN 2011 TENTANG PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN - Tiara Rizky Monica; Dessy Artina; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
This study aims to determine the management of land and building taxes as local revenue for the city of Pekanbaru based on Regional Regulation Number 8 of 2011 concerning Rural and Urban Land and Building Taxes. This research uses the type of research that is empirical research or sociological legal research. The analytical tool in this study is a qualitative way. This research found that there are things that are not optimal in reality in the field, so it is necessary to anticipate with maximum effort and optimization. This study concludes that each year the City Government has a target in receiving Land and Building Tax (PBB) as a source of regional income, but this target has not been fully realized. Sometimes the realization of Land and Building Tax (PBB) revenue is far below the target set by the City Government. Based on the recapitulation data of Land and Building Tax revenue in the last 3 years (2017-2020) from the results of this temporary research it can be said that it has not been carried out optimally and has not been able to achieve as the target has been set, this can also be seen from the increasing awareness of Obligators. Sometimes the realization of Land and Building Tax (PBB) revenue is far below the target set by the City Government. It is necessary to identify variables related to efforts to increase land and building tax revenue as well as actions / efforts that may need to be taken to use the potential for land and building tax that is not yet optimal. One of the policies and strategies that local governments can do to increase local revenue is calculating potential revenue. Keywords: Optimization - Property tax - Pekanbaru City Original Revenue